Life satisfaction among Spanish children and adolescents participating in Physical Education - Gómez-Paniagua, Santiago; Castillo-Paredes, Antonio; Galán-Arroyo, Carmen; Rojo-Ramos, Jorge (Frontiers in Public Health, 2024)
Life satisfaction has been determined as a cognitive indicator of subjective wellbeing, a term that acquires vital relevance during adolescence as a protective factor against numerous psychological, mental and social disorders. Therefore, the objectives of this study are: 1) to evaluate differences in life satisfaction as a function of gender and school environment in Spanish children and adolescents; and 2) examine the possible associations between life satisfaction and age and/or body mass index (BMI) of the student body. For this purpose, a cross-sectional study was carried out with 723 students (aged 6 to 18 years) in which the "Satisfaction with life Scale" was applied, consisting of 5 items that measure self-perception of life satisfaction. Nonparametric statistics (Mann-Whitney U test) were used to explore differences in scores according to sex and school environment, in addition to Spearman's Rho test to identify associations between scale scores and students' age and BMI. Significant differences were obtained in terms of sex in favor of the male gender, and between the two environments of the centers in favor of the rural ones. In addition, the two variables explored (age and BMI) showed significant inverse associations with life satisfaction levels. Therefore, educational interventions and policies must take this information into account to design and develop actions aimed at improving this cognitive factor.